INVESTIGATING UNIVERSITY STUDENTS’ ABILITY IN PARAPHRASING PARAGRAPHS - Cindy Hannisya Relia; Afrianto Daud; Syofia Delfi (International Journal of Educational Best Practices, 2021)
This research examined university students’ ability in paraphrasing paragraphs. This descriptive quantitative research took students of the English Education Department of Universitas Riau as samples using cluster random sampling technique. The selected sample was a Class of the English Study Program, Universitas Riau, which consists of 34 students. The data were collected by administering an online test of paraphrasing paragraphs through Google Form. The collected data were analyzed by three raters and the results were calculated and classified by using adaptation guide rubric from Brown (2004). Three aspects of paraphrasing were assessed and analyzed: contents of information, choice of words and writing convention. This study found that the ability of the Students of English Study Program in paraphrasing paragraphs was an unacceptable level, with total points; 11.21 for Content Information aspect, 9.52 for Choice of Words aspect, and 9.75 for Writing Conventions aspect. In order to answer the research question on how bad the ability is, the only clear answer is that all facts that are found within the research are only referring to the ‘crisis’ of paraphrasing ability shown by the university students themselves. This finding showed that the university students’ ability in paraphrasing paragraphs is low, due to the facts that; First, they get a low-level score in all aspects of paraphrasing. Second, they still make many fatal mistakes in every aspect of paraphrasing like; skipping important details in paraphrasing that may lead to misinformation, misusing the vocabulary and diction in creating the words in paraphrasing, and severe problems in the grammar, punctuation, and spelling (writing conventions). Moreover, choice of words seems to be the most difficult aspect for the students since it had the lowest score than other aspects in paraphrasing. This research suggests that English students should be exposed to more practices in their academic writing subject about paraphrasing skills